Effects of Zeaxanthin on Growth and Invasion of Human Uveal Melanoma in Nude Mouse Model. (22nd November 2015) - Xu, Xiaoliang L.; Hu, Dan-Ning; Iacob, Codrin; Jordan, Adrienne; Gandhi, Sandipkumar; Gierhart, Dennis L.; Rosen, Richard
Abstract : Uveal melanoma cells were inoculated into the choroid of nude mice and treated with or without intraocular injection of zeaxanthin. After 21 days, mice were sacrificed and the eyes enucleated. Histopathological analysis was performed in hematoxylin and eosin stained frozen sections. Melanoma developed rapidly in the control group (without treatment of zeaxanthin). Tumor-bearing eye mass and tumor mass in the control group were significantly greater than those in zeaxanthin treated group. Melanoma in the controlled eyes occupied a large part of the eye, was epithelioid in morphology, and was with numerous mitotic figures. Scleral perforation and extraocular extension were observed in half of the eyes. Melanomas in zeaxanthin treated eyes were significantly smaller with many necrosis and apoptosis areas and no extraocular extension could be found. Quantitative image analysis revealed that the tumor size was reduced by 56% in eyes treated with low dosages of zeaxanthin and 92% in eyes treatment with high dosages of zeaxanthin, as compared to the controls. This study demonstrated that zeaxanthin significantly inhibits the growth and invasion of human uveal melanoma in nude mice, suggesting that zeaxanthin may be a promising agent to be explored for the prevention and treatment of uveal melanoma.